Environmental Effects Of Ecotourism In Indonesia - Butarbutar, Regina; Soemarno, Soemarno (Journal of Indonesian Tourism and Development Studies, 2013)
The ecotourism is global issues who most talked lately in Indonesia, it is one of the activities special tourist interest which low impacts on natural tourism.The presence of ecotourism in the era of sustainable and tourism development mission should be minimum negative impacts, both on the environment resources and on socio-cultural local values. Ecotourism activities were more oriented on the utilization of natural resources, the natural ecosystems and have not been polluted yet. However, when all of tourism development can not be separated from the negative impacts, such as ecosystem distress in ecotourism object when visited by large number of tourists, there are many conflicts of interest between the ecotourism management with local communities, especially regarding the benefits sharing and its accessibilities. The purpose of this paper is to identify the environmental impacts arising as a result of ecotourism activities and to find out alternative efforts in mitigating the environmental impact of ecotourism activities. Carrying capacity of ecotourism is not just limited to the number of visits, but also covers other aspects, such as: (1 ) ecological capacity that is ability of natural environment in providing the needs of tourists, (2) physical capacity, that is ability of facilities and infrastructure in providing the needs of tourists,  (3) social capacity, that is ability to absorb tourism activities without the negative impacts on the local communities, (4) the economic capacity, that is ability to absorb destination commercial efforts and accommodateany interests of the local economy. Keywords: Ecotourism, environmental impacts, carrying capacity.